EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGRAAN - Sulviani, Sulviani; Achmadi, Achmadi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe present research aimed to know the effectiveness of using images to inprove the tenth grade students of MAN 2 Pontianak’s learning results in Pancasila and Civics Education  subject. This research used experimental method with  one Pretest-Group Post-test desig. The findings showed that the use of pictures effectively improve the students’ learning results. In advance of using pictures as a teaching medium, the average score of the students 64.45 with the lowest score of 40 and the highest of 90. After pictures were used, however, the average score significantly rose to 76,21 the lowest score of 40 and the highest of 95. based on the t test on  of it was known that the sig(2-tailed) was 0.001, smaller than 0,05 with 3.727 t count. The value of sig was 0.001<0.005. it can be concluded that the use of pictures is effective in improving   grade of learning result in Pancasila and Civic Education subject. The effect size test showed that the value of the effectiveness of using pictures was 0.59. It can be concluded that the use of pictures is effective in improving the learning results of students of MIPA 4 tenth grade class of MAN 2 Pontianak.Keywords: Learning Results, Picture, Pancasila and Civic Education subject’s students